3D geospatial technique in analysing the Malay heritage building structures - Abdullah, Ahmad Afiq Aiman; Hj. Mohd. Noor, Norzailawati; Abdullah, Alias; Ali, Maisarah; Mustafa, Muhammad Hadi (Malaysian Institute Of Planners, 2020)
Malay buildings are synonym with the unique design of full decorative on motive, unique façade design, and roof structured. Most of heritage buildings had been demolished and left out without proper documentation and preserving the building database. Latest mapping systems provide an efficient technique for acquiring dense point clouds in analysing the building structure. This paper aim to explore on the technique acquiring the data for distribution and the façade of building with the Malay architecture design using the laser scanning. Data acquisition was taken for two sites which are Kota Bharu, Kelantan and Alor Setar, Kedah with two different techniques were applied for data collection which are TLS and MLS method. Both methods had succeed in capturing the detail of the features and building in the study area in point cloud form and the analysis of the data was able to analysed on the classification and identification of the Malay building elements and features which still preserved Malay design at the facade and roof element in the study area. As the final results and findings, there were big gaps between the building which still preserved the Malay design in the study area where Kota Bharu recorded 71 units building meanwhile Alor Setar only 15 buildings. The results showed that, most of the Traditional Malay building still being preserved in Kota Bharu compared to Alor Setar.